Kinetics of lipase production from candida cylindracea by solid-state bioconversion of palm kernel cake - Alam, Md Zahangir; Elgharbawy, Amal Ahmed; Mohd Salleh, Hamzah (Academy of Agricultural Sciences, NAAS, India, 2014)
Solid- state bioconversion (SSB) of palm kernel cake (PKC) by Candida cylindracea is a cost-effective method to produce lipase from abundant raw material in Malaysia. This study was conducted to describe the growth profile of Candida cylindracea on PKC using SSB. Since separating yeast cells (biomass) is not a feasible task, indirect method was used to monitor the growth during the fermentation process. This method was based on glucosamine, protein and carbohydrate content of the fermented media during the fermentation period. The results showed that the pH of the fermented PKC increased from 6.1 to 8.5 at the first 60 h and turned to neutral after that. Protein concentration of the fermented medium started to decrease within the first 24 h, and then increased gradually. Total carbohydrates decreased from 290 mg/g PKC to reach 155 mg/g PKC by the end of the fermentation. Glucosamine, a component in the mycelia cell walls, was measured to monitor the biomass during the fermentation. Maximum concentration of glucosamine achieved after 72 h and started to decrease to almost stable for the next hours. This data can be used to have a good understanding of the fermentation process and the lipase production.